Five Configurations of Opportunism in International Market Entry - Verbeke, Alain; Ciravegna, Luciano; Lopez, Luis E.; Kundu, Sumit K. (Journal of Management Studies, 2019)
We investigate the conditions under which opportunism occurs in international market entry. Examining 133 entries into new markets by 38 Chinese exporters, we uncover instances of opportunistic behaviour on the part of importers. We study five variables affecting such behaviour: managerial experience, market entry share; market distance, young age, and network size . While we find no single variable on its own associated with opportunism, we do find that in concert they form five configurations of opportunism. In one configuration, even older firms with experienced managers and a large network are subject to partners behaving opportunistically when they are entering a distant market. We conclude that simplistic predictions based on the presence of a single antecedent should make way for a configurational approach whereby a set of conditions must be in place for opportunism to materialize.